Børn, billeder og personlighedsdannelse - Nielsen, Anne Maj (Psyke & Logos, 2023)
The article presents some genderspecific characteristics in children ’sart and a concept of different symbol-layers. Analyzing children’s art the concept is useful. Genderspecific characteristics in children’ s art are described according to the concept of relative development emphasizing that pictures made by children are strongly inspired by pictorial language and motifs in culture. At the same time, however, children’s art is expressing personally important themes and questions actualized in children’s lives and development. The concept of symbol-layers, namely a cultural symbol-layer, a local symbol-layer and a personal symbol-layer, is presented in order to develop a tool to grasp the processes of inspiration and influence from pictures in culture to the individual as well as the spontaneous creativity of the individual in the culture.